2018
DOI: 10.1016/j.resourpol.2018.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Landfill mining from extractive waste facilities: The importance of a correct site characterisation and evaluation of the potentialities. A case study from Italy

Abstract: At present, little information is available on the opportunities and challenges to recover valuable critical raw materials (CRM) and secondary raw materials (SRM) from extractive waste (EW) deposits. In this study, an integrated framework describing the key steps required to assess the viability of CRM recovery from EW deposits is presented. The framework has been tested and validated using a pilot site located in the Northern region of Lombardy, Gorno. A tiered characterisation approach was used to support th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 21 publications
0
28
0
1
Order By: Relevance
“…Preliminary data (XRD and XRF) on selected samples show a fair amount of kaolin and a very low Fe 2 O 3 content, suggesting a hydrothermal origin (quartz veins, presence of tourmaline) and a good suitability for the ceramic industry. Finally, the chance to exploit the other kaolinitic gneisses on the slopes of Monte Bracco should be further evaluated: If the reuse of quartzite waste and kaolin-rich gneisses are feasible, a more targeted field geological survey, physical, chemical and mineralogical characterization of the potential deposit and total volume estimation (field and GIS investigations) are recommended [16]. In the perspective of sustainable mining, it is important to move towards an integrated exploitation of the Monte Bracco area, with contemporary exploiting of the quartzite bench (second class material-quarrying activity), the quartzite waste and the kaolinitic gneisses (first class materials-mining activity for industrial minerals).…”
Section: Discussion and Perspectives: Sustainable Mining Of The Minermentioning
confidence: 99%
“…Preliminary data (XRD and XRF) on selected samples show a fair amount of kaolin and a very low Fe 2 O 3 content, suggesting a hydrothermal origin (quartz veins, presence of tourmaline) and a good suitability for the ceramic industry. Finally, the chance to exploit the other kaolinitic gneisses on the slopes of Monte Bracco should be further evaluated: If the reuse of quartzite waste and kaolin-rich gneisses are feasible, a more targeted field geological survey, physical, chemical and mineralogical characterization of the potential deposit and total volume estimation (field and GIS investigations) are recommended [16]. In the perspective of sustainable mining, it is important to move towards an integrated exploitation of the Monte Bracco area, with contemporary exploiting of the quartzite bench (second class material-quarrying activity), the quartzite waste and the kaolinitic gneisses (first class materials-mining activity for industrial minerals).…”
Section: Discussion and Perspectives: Sustainable Mining Of The Minermentioning
confidence: 99%
“…Site description, which consists of collection of information about geology, mining, and processing activities (Section 2.1) [33] 2. Site investigation and sampling strategy (Section 2.2), which includes planned field survey to collect representative samples, define the investigating areas, evaluate waste characteristics, and estimate EW volumes [33] 3. Preparation of sub sample to be tested for RM/CRM recovery (Section 2.3)…”
Section: Methodsmentioning
confidence: 99%
“…The sampling was performed in dumps placed at Mount Arera ( Figure 3) following site investigation and sampling activities described in Dino et al [33] and here briefly reported. The WR dumps at Mount Arera are spread uniformly with thickness of c. 2 m. Waste rock material was sampled using a hand shovel and/or a hammer.…”
Section: Site Investigation and Sampling Strategymentioning
confidence: 99%
See 2 more Smart Citations